Perkembangan Pola Permukiman Tradisional Berbasis Kearifan Lokal: Studi Kasus: Kampung Enggros dan Kampung Tobati di Kota Jayapura - Awal Purnama Putra; Deasy Widyastomo; Sudiro Sudiro (Fakultas Teknik Universitas Cenderawasih, 2024)
The development of Jayapura City as the capital of Papua Province has grown into a region very rapidly from being a modern city. The classification of areas in Jayapura City is included in the heterogeneous area group where the types of population come from various tribes and regions that live in Jayapura City. The city of Jayapura has land and sea areas with different areas, and has residential characteristics as a traditional village. The settlements of Kampung Enggros and Kampung Tobati are located around the coast of Yotefa Bay, including in the South Jayapura District and Abepura District of Jayapura Municipality, where the community builds their settlements above sea water. One thing that residents will face is the relationship between humans and the places where they live, which cannot be separated from nature. The research methods used to achieve the objectives of this research are comparative analysis and qualitative methods. The comparative analysis method displays settlement patterns with comparisons between 2019-2023 in the form of images. Qualitative descriptive analysis method by presenting actual settlement development problems in the field in the form of pictures. The research results show that there are 3 factors for settlement development in Enggros and Tobati Villages, namely, Community, Protection and Network. Society is changing from traditional to modern, for example traditional houses become modern houses that keep up with the times. The network turns into a spatial structure in a pattern that is influenced by the economic aspects of indigenous communities. The main thing is natural factors because in the general view of indigenous Papuans, what is meant by their home is the natural surroundings where they can live.